2015
DOI: 10.1002/eji.201545734
|View full text |Cite
|
Sign up to set email alerts
|

Protease activity of Per a 10 potentiates Th2 polarization by increasing IL‐23 and OX40L

Abstract: Proteases are implicated in exacerbation of allergic diseases. In this study, the role of proteolytic activity of Per a 10 was evaluated on Th2 polarization. Intranasal administration of Per a 10 in mice led to allergic airway inflammation as seen by higher IgE levels, cellular infiltration, IL-17A, and Th2 cytokines, whereas, inactive ( )Per a 10 showed attenuated response. There was an increased OX40L expression on lung and lymph node dendritic cells in Per a 10 immunized group and on Per a 10 stimulated BMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…Previously, we have shown that Per a 10, a major serine protease allergen from Periplaneta americana , activates DCs to secrete higher levels of IL‐23 and a lower level of IL‐12p70. A downregulation of IL‐12p35 and an upregulation of IL‐23p19 levels were observed in mouse lungs upon intranasal administration of Per a 10 and blocking of IL‐23 led to a reduction in the levels of Th2 cytokines in DC‐T‐cell coculture studies . However, the mechanisms which differentially regulate the secretion of cytokines by dendritic cells upon activation by protease allergens are not understood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have shown that Per a 10, a major serine protease allergen from Periplaneta americana , activates DCs to secrete higher levels of IL‐23 and a lower level of IL‐12p70. A downregulation of IL‐12p35 and an upregulation of IL‐23p19 levels were observed in mouse lungs upon intranasal administration of Per a 10 and blocking of IL‐23 led to a reduction in the levels of Th2 cytokines in DC‐T‐cell coculture studies . However, the mechanisms which differentially regulate the secretion of cytokines by dendritic cells upon activation by protease allergens are not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytically active Per a 10 leads to a downregulation of IL‐12p35 and an upregulation of IL‐23p19 at transcript level. Inactivation of protease activity attenuates allergic immune responses . In the present study, we have elucidated the mechanism by which protease activity of Per a 10 activates dendritic cells to create a cytokine milieu rich in IL‐23 and deficient in IL‐12p70 and leads to Th2 polarization.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations